Using benthic macroinvertebrate distribution and water quality as organic pollution indicators for fish farming areas in Rawang sub-basin, Selangor River, Malaysia: a correlation analysis - Hettige, Nadeesha Dilani; Hashim, Rohasliney; Abas Kutty, Ahmad; Ash’aari, Zulfa Hanan; Jamil, Nor Rohaizah (Faculty of Fisheries, Kasetsart University, Thailand, 2022)
Fish farming activities are essential to the economy of many countries. However, the discharge of fish farm effluents into nearby rivers can negatively impact benthic macroinvertebrates and water quality. In Malaysia, the correlation between water quality and benthic macroinvertebrates in areas impacted by fish farming has not been discussed comprehensively. Hence, this research investigated the connection between benthic communities and water quality in the Rawang sub-basin of the Selangor River using several statistical methods. Based on ease of accessibility and proximity to freshwater fish farms, and by using a random sampling method, seven sampling sites in six rivers were chosen including one reference site. Sampling of benthic macroinvertebrates and river water was carried out between April 2019 and March 2020. Principal Component Analysis (PCA) revealed that fish farming operations influence various water quality parameters such as dissolved oxygen (DO), biochemical oxygen demand (BOD5), chemical oxygen demand (COD), total suspended solids (TSS), pH, and ammonia-nitrogen. Canonical Correspondence Analysis (CCA) revealed that families Aeolosomatidae, Chironomidae, Lumbriculidae, Naididae, Planorbidae, and Tubificidae are tolerant to organic pollution. Their abundance was correlated with high BOD5, COD, turbidity, TSS, and ammonia-nitrogen. On the other hand, the families Caenidae, Gomphidae, Aytidae, Leptophlebiidae, Thiaridae, and Viviparidae are sensitive to organic pollution and were correlated with DO concentration. This research revealed that the correlation between benthic macroinvertebrate communities and water quality in the area is affected explicitly by fish farms.